PEMEROLEHAN BAHASA TELEGRAM DAN KALIMAT ANAK USIA PRASEKOLAH DAN SD - Siti Djuwarijah (Universitas Islam Balitar, 2017)
This study investigated acquisition in Bahasa Indonesia by children learning in playgroup and SD in Mataram. This study used ethnograpic and psycholinguistic as the design. Subject of the study were 6 students of playgroup aging 3-4 years and 4 SD students at 11-12 age. Data were collected using observation and interview. The study revealed that: (1) children learning at playgroup at age 3-4 used telegraphic utterance applying content words to convey message. Phonemes and morphology were aspired in terms of incomplete sound and spelling; (2) children at age 11-12 years old learning in the fifth grade of SD used syntac in terms of sentences. Sentences had been produced in terms of subject, predicate, object, adverbs, that function as parts of speech as the development of vocabulary and diction also improved.